Moisture and density data of sediment cores from Meteor cruise M167 - Walter Menapace (PANGAEA, 2023)
Moisture And Density data (water content, bulk density and porosity) from sediment samples collected during the RV Meteor M167 expedition in the Gulf of Cadiz and Alboran Sea between 11.10.2020 and 05.11.2020. Samples were collected and weighted onboard, whereas the Moisture And Density parameters were measured at MARUM with a helium pycnometer.